2011
DOI: 10.1007/s00296-011-1887-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of reclassification of World Health Organization (WHO) class III under International Society of Nephrology-Renal Pathology Society (ISN-RPS) classification: retrospective observational study

Abstract: The outcome of systemic lupus erythematosus (SLE) is largely influenced by the existence of lupus nephritis (LN), and its histologic classification guides the treatment and prognosis of SLE. International Society of Nephrology-Renal Pathology Society (ISN-RPS) announced a revised classification of LN in 2004. The present study investigated the differential outcome of World Health Organization (WHO) class III LN when reclassified according to ISN-RPS classification. Forty-three patients with biopsy-proven WHO c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We summarized the findings of interobserver validation studies in the literature in Table 3 . Standardization of the definitions for each class with clear discriminating criteria and a well-defined approach in the handling of sclerotic glomeruli improved both intraobserver and interobserver reproducibility and enabled reliable comparison of different cases from various centers [ 13 , 22 26 ]. Moreover, the morphologic parameters indicative of prognostic value and outcome contributed to the medical literature.…”
Section: What Is New In 2004 Isn/rps Lupus Nephritis Classificatiomentioning
confidence: 99%
“…We summarized the findings of interobserver validation studies in the literature in Table 3 . Standardization of the definitions for each class with clear discriminating criteria and a well-defined approach in the handling of sclerotic glomeruli improved both intraobserver and interobserver reproducibility and enabled reliable comparison of different cases from various centers [ 13 , 22 26 ]. Moreover, the morphologic parameters indicative of prognostic value and outcome contributed to the medical literature.…”
Section: What Is New In 2004 Isn/rps Lupus Nephritis Classificatiomentioning
confidence: 99%
“…6 There are a number of reports showing that ISN/RPS classifications correlate well with renal prognosis in LN. [7][8][9][10][11][12] While ISN/RPS classifications principally depend on glomerular pathology, extra-glomerular lesions such as interstitial fibrosis, tubular atrophy and vasculopathy are risk factors for renal outcome. 13,14 Therefore, recent guidelines recommend that all patients with clinical evidence of active LN undergo renal biopsy to obtain information necessary for making decisions on treatment and management of nephritis.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant group differences in outcomes were detected. Similarly, Hwang and coworkers reported that among 43 patients with WHO class III LN, 12 patients were reclassified into ISN/RPS class IV (class IV-S, n = 9; class IV-G, n = 3) 8) . At one-year follow-up, there were no group differences in the response to treatment.…”
Section: Prognosis In Who Class IVmentioning
confidence: 99%
“…PR was defined as sCr<1.4 mg/dl and urinary protein decreased by 50% or more from baseline or 1+ to 2+ by dipstick test. NR was defined as a deterioration in renal function exclusive of other causes (such as sepsis or nephrotoxic agents), a reduction in urinary protein with failure to reach PR, or the persistence of active urinary sediments (<10 RBC/HPF) 8) . Renal flare was defined as an increase in urinary protein of 1 g/gCr associated with an increase in serological activity.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation